Parental responsiveness and children’s trait epistemic curiosity - Iwasaki, Shoko; Moriguchi, Yusuke; Sekiyama, Kaoru (Frontiers in Psychology, 2023)
Curiosity, the desire to learn new information, has a powerful effect on children’s learning. Parental interactions facilitate curiosity-driven behaviors in young children, such as self-exploration and question-asking, at a certain time. Furthermore, parenting quality predicts better academic outcomes. However, it is still unknown whether persistent parenting quality is related to children’s trait epistemic curiosity (EC). The current study examined whether parenting practices, responsiveness, and demandingness are cross-sectionally related to the trait EC of children in different age groups (preschoolers, younger schoolers, and older schoolers). We adopted a shortened Japanese version of the parenting style questionnaire (Robinson, Mandleco, Olsen, & Hart, 1995) and modified the trait EC questionnaire in young children (Piotrowski, Litman, & Valkenburg, 2014). A sample of 244 caregivers (87.37% mothers) of children (ages 3–12) was recruited through educational institutions in Japan and reported on their parenting practices and trait EC. All data analyses were performed using SPSS version 26. Hierarchical regression analyses were performed to determine the explanatory variables for children’s trait EC. Self-reported parental responsiveness significantly explained EC scores. To the best of our knowledge, this is the first study to show a cross-sectional relationship between parental responsiveness and children’s trait EC. Future research should clarify whether parental responsiveness in early childhood predicts children’s EC later in life.